2022
DOI: 10.3390/biomedicines10123168
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Oral Cannabinoids in People Living with HIV on Long-Term ART: A Randomized, Open-Label, Interventional Pilot Clinical Trial (CTNPT 028)

Abstract: Background: With anti-inflammatory properties, cannabinoids may be a potential strategy to reduce immune activation in people living with HIV (PLWH) but more information on their safety and tolerability is needed. Methods: We conducted an open-label interventional pilot study at the McGill University Health Centre in Montreal, Canada. PLWH were randomized to oral Δ9-tetrahydrocannabinol (THC): cannabidiol (CBD) combination (THC 2.5 mg/CBD 2.5 mg) or CBD-only capsules (CBD 200 mg). Individuals titrated doses as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…This study found that patients did not show safety concerns, and it was well-tolerated. However, there was no report about inflammatory levels, CD4 cell count, viral load, co-morbidities, etc 66 . Incorporating CBD or THC as therapeutic agents for HIV patients still requires more investigation to collect evidence on the HIV disease progression, viral latency, interaction with ART regimens, neurocognition, safety, and other co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that patients did not show safety concerns, and it was well-tolerated. However, there was no report about inflammatory levels, CD4 cell count, viral load, co-morbidities, etc 66 . Incorporating CBD or THC as therapeutic agents for HIV patients still requires more investigation to collect evidence on the HIV disease progression, viral latency, interaction with ART regimens, neurocognition, safety, and other co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…An additional layer of complexity is introduced by the dual nature of THC as both a partial agonist and antagonist for CB1R. Furthermore, THC can interact with other endocannabinoid receptors to exert anti-inflammatory effects [ 230 , 232 ].…”
Section: Clinical Applications and Challengesmentioning
confidence: 99%
“…The study also found that despite the use of medical cannabis, the majority of patients taking antidepressants and anxiolytic medications did not change their medications or the dose of these medications. Bouassa et al, found that THC and CBD were well-tolerated by patients with HIV on anti-retroviral therapy [ 9 ]. Their study did find that patients on high doses of CBD (800 mg/day) should be monitored for liver pathology.…”
Section: Original Research Articlesmentioning
confidence: 99%